Design and Development of a Cost-Effective Hydraulic Screw Jack-Based Punch-Die System for Small-Scale Manufacturing - Mohsin Lalabhai Shaikh; Vishal Suresh Kadam (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
This paper presents the design and development of a cost-effective punch-die system integrated with a hydraulic screw jack for small-scale sheet metal manufacturing applications. Conventional punching machines are often expensive, bulky, and dependent on external power sources, making them unsuitable for rural workshops, cottage industries, and educational laboratories. The proposed system addresses these limitations through a compact, frame-based design fabricated from mild steel and equipped with a 10-ton manual hydraulic screw jack. The punch and die, manufactured from EN31 and H13 tool steels, respectively, ensure durability and precision in operations such as washer fabrication. Finite Element Analysis (FEA) was conducted to evaluate stress distribution and load-bearing capacity, confirming structural safety and minimal deflection under maximum load conditions. Experimental validation demonstrated consistent punching performance for mild steel sheets up to 3–5 mm thickness, with accurate force transmission, safety, and ease of operation. The system is portable, low-maintenance, and adaptable through interchangeable die sets, making it a versatile tool for training, prototyping, and small-scale production. By eliminating dependence on electricity and high-cost machinery, this design provides a practical solution for resource-constrained environments and offers significant potential for adoption in MSMEs and vocational education.
Keywords: Punch-die system; Hydraulic screw jack; Frame design; Cost-effective manufacturing; Sheet metal punching; Small-scale industries